Herbal Plant Education and Hydroponic Training of Vertical and Wick System in Limited Space - Andini, Ary; Prayekti, Endah; Romdloni , Muhammad Afwan; Rhomadhoni , Muslikha Nourma; Sofaria Munir, Ratna (Universitas Nahdlatul Ulama Surabaya, 2024)
The program